2007
DOI: 10.1111/j.1445-2197.2007.04141.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of Non‐randomized Comparative Studies of the Short‐term Outcomes of Laparoscopic Resection for Colorectal Cancer

Abstract: Laparoscopic resection remains to be established as the procedure of first choice for operable colorectal cancer. The aim of the study was to conduct a systematic review of non-randomized comparative studies of laparoscopic resection for colorectal cancer. Published work in English was searched for relevant articles published by the end of 2003. The MOOSE statement was used to conduct the meta-analysis. Study quality was assessed by two investigators using the MINORS tool and the analysis was conducted using C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
121
2
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(137 citation statements)
references
References 62 publications
5
121
2
9
Order By: Relevance
“…Conventional MLC has been proven to be oncologically equivalent to OC, in terms of recurrence and survival [53,[60][61][62]. Therefore, any new surgical treatment against colon cancer has to be evaluated in terms of oncological radicalness, compared with MLC, which till nowadays serves as a gold standard [50,[63][64][65][66]. In the present study, all resection margins were free from tumor.…”
Section: Discussionmentioning
confidence: 75%
“…Conventional MLC has been proven to be oncologically equivalent to OC, in terms of recurrence and survival [53,[60][61][62]. Therefore, any new surgical treatment against colon cancer has to be evaluated in terms of oncological radicalness, compared with MLC, which till nowadays serves as a gold standard [50,[63][64][65][66]. In the present study, all resection margins were free from tumor.…”
Section: Discussionmentioning
confidence: 75%
“…However, all patients were successfully operated laparoscopically. Abraham et al reviewed studies, which contained more than 6438 patients of LAR and reported a conversion rate of 7.7% [4]. Shek et al reported a conversion rate of 4% in his series of 99 patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…Under conventional circumstances, in the first published series of 20 laparoscopic sigmoid colectomies, the authors reported that a five-day hospital stay was achieved in 70% of patients. However, subsequent larger studies including randomized trials reported an average length of stay of about eight days which is still an improvement of about 20% compared with conventional open resections (Abraham et al, 2004(Abraham et al, & 2007Schwenk et al, 2005). The last published large randomized controlled trial of the topic (The ALCCaS) showed no statistically significant difference in postoperative complications, reoperation rate, or perioperative mortality between laparoscopic and open resections (Allardyce et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Large published studies, randomized trials and meta-analyses suggest an average length of hospital stay of about ten days (Bokey et al, 1995;Abraham et al, 2004Abraham et al, & 2007. In an attempt to mimic the success of laparoscopic gall bladder surgery, laparoscopic colorectal resection was introduced in 1991 as a proposed less invasive alternative to the open technique (Jacobs, 1991;Redwine, 1991).…”
Section: Introductionmentioning
confidence: 99%